Librarian’s Information Literacy Skills to Fulfilling Library Users' Needs A Public Library in Bogor, Indonesia - Hasanah, Alfia; Rachman, Margareta Aulia (Record and Library Journal, 2019)
Background of the study: literacy skills of librarianPurpose: This study aims to identify the information literacy skills of librarians in meeting the information needs a user at the public library in the city of Bogor.Method: This study used a qualitative approach with the case study method. Data were collected through observation and interview. The informants of six people selected using purposive sampling, with the criteria set librarian of Library Science education. Information literacy models used in this study are a model Empowering Eight, consisting of identification, exploration, selection, organization, creation, presentation, assessment and application information..Findings: The results showed that the information literacy librarian at the public library in the city of Bogor in meeting the information needs user already applied include a component on the identification, exploration, presentation, assessment, and application.Conclusion: There are some capabilities that cannot be applied to the maximum, including component selection, organization and creation of information.